Interleukin-6, Cortisol, and Brain-Derived Neurotrophic Factor as Biomarkers of the Severity of Traumatic Brain Injury and Its Complications in the Acute and Long-Term Periods: Results of a Prospective Study - S. I. Balan; A. A. Belikova; I. G. Komoltsev; A. V. Timokhova; T. A. Druzhkova; A. E. Talypov; A. B. Guekht; N. V. Gulyaeva (Neuroscience and Behavioral Physiology, 2026)

Preservation of organic traces of life under Martian conditions: Influence of the nature of the smectite in presence - I. Criouet; S. Bernard; E. Balan; F. Baron; A. Buch; F. Skouri-Panet; M. Guillaumet; L. Delbes; L. Remusat; J.-C. Viennet (Icarus, 2026)

High-resolution solid-state 7Li NMR study of lithium incorporation in calcite and aragonite - A. Zhadan; V. Montouillout; J. Aufort; V. Mavromatis; E. Balan (Chemical Geology, 2025)

Lateritic Cenozoic paleoenvironmental and paleoclimatic conditions in the Central Amazon basin, Brazil, inferred from mineralogy, geochemistry and geochronology - C. Ansart; D. Guinoiseau; C. Quantin; D. Calmels; C. Gautheron; P. Agrinier; J. Bouchez; Z. Fekiacova; R. Pinna-Jamme; D. Demri; E. Balan; B. Heller; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Impact of UV radiation on the Raman and infrared spectral signatures of sulfates, phosphates and carbonates: Implications for Mars exploration - C. Royer; S. Bernard; O. Beyssac; E. Balan; O. Forni; M. Gauthier; M. Morand; Y. Garino; P. Rosier (Icarus, 2024)

Effect of IGFBP6 Knockdown on Proteins Regulating Exosome Synthesis and Secretion in MDA-MB-231 Cell Line - A. S. Efimova; I. D. Antipenko; E. A. Evtushenko; P. V. Balan; S. A. Tonevitskaya (Bulletin of Experimental Biology and Medicine, 2023)

Quantitative Assay of SARS-CoV-2 RNA and Level of Proinflammatory Protein Gene Transcripts in Peripheral Blood Leukocytes after a Novel Coronavirus Infection - L. V. Topchieva; O. V. Balan; A. V. Men’shenin; I. E. Malysheva; E. L. Tikhonovich (Bulletin of Experimental Biology and Medicine, 2022)

Phytotoxicity in Seedlings of Rhizophora mangle (L.) Exposed to 2,4-Dichlorophenoxyacetic Acid under Experimental Conditions - Carlos A. Chan-Keb; Claudia M. Agraz-Hernández; Román A. Pérez-Balan; Eduardo J. Gutiérrez-Alcántara; Raquel Muñiz-Salazar; Jordán E. Reyes-Castellano; Juan Osti-Sáenz (Journal of Marine Science and Engineering, 2021)
Mangroves are considered one of the most productive ecosystems worldwide, providing multiple environmental goods and services; however, in recent years, there have been modifications and deterioration in the structure and function of these ecosystems, caused by various natural events and anthropic activities, such as the construction of roads, wastewater discharge, unsustainable livestock, and agricultural practices, as well as the impact of chemicals, such as heavy metals, oil spills, and the use of herbicides. In this research, phytotoxic effects on seedlings of Rhizophora mangle were evaluated at an exposure of five dilutions w/v (5%, 10%, 25%, 50%, and 100%) of the commercial presentation of 2,4-dichlorophenoxyacetic acid (2,4-D). Propagules grown in a greenhouse under local tidal regimes were used, so the growth of stem diameter, height, biomass production in root, leaves, and stems, as well as the concentration of chlorophyll a of the exposed seedlings were measured. The comparison of these parameters in seedlings with only seawater presented significant differences (p ≤ 0.05) and inhibitory effects on growth (diameter), the stem concentration of chlorophyll a, and the production of biomass of leaves, stems, and roots. The inhibitory effect of exposure to 2,4-D on chlorophyll production and root biomass is highlighted, with an average decrease of 45% relative to the control. The sensitivity of the Rhizophora mangle seedlings to the applied concentrations of herbicide evidence the inhibitory effects on the morphological variables of biomass production and chlorophyll a production in mangrove leaves.

An agenda for research and action toward diverse and just futures for life on Earth - C. Wyborn; J. Montana; N. Kalas; S. Clement; F. Davila; N. Knowles; E. Louder; M. Balan; J. Chambers; L. Christel; T. Forsyth; G. Henderson; et al. (Conservation Biology, 2021)
Decades of research and policy interventions on biodiversity have insufficiently addressed the dual issues of biodiversity degradation and social justice. New approaches are therefore needed. We devised a research and action agenda that calls for a collective task of revisiting biodiversity toward the goal of sustaining diverse and just futures for life on Earth. Revisiting biodiversity involves critically reflecting on past and present research, policy, and practice concerning biodiversity to inspire creative thinking about the future. The agenda was developed through a 2‐year dialogue process that involved close to 300 experts from diverse disciplines and locations. This process was informed by social science insights that show biodiversity research and action is underpinned by choices about how problems are conceptualized. Recognizing knowledge, action, and ethics as inseparable, we synthesized a set of principles that help navigate the task of revisiting biodiversity. The agenda articulates 4 thematic areas for future research. First, researchers need to revisit biodiversity narratives by challenging conceptualizations that exclude diversity and entrench the separation of humans, cultures, economies, and societies from nature. Second, researchers should focus on the relationships between the Anthropocene, biodiversity, and culture by considering humanity and biodiversity as tied together in specific contexts. Third, researchers should focus on nature and economies by better accounting for the interacting structures of economic and financial systems as core drivers of biodiversity loss. Finally, researchers should enable transformative biodiversity research and action by reconfiguring relationships between human and nonhuman communities in and through science, policy, and practice. Revisiting biodiversity necessitates a renewed focus on dialogue among biodiversity communities and beyond that critically reflects on the past to channel research and action toward fostering just and diverse futures for human and nonhuman life on Earth.

The Role of Inducible NOS2 Gene Polymorphism in the Development of Essential Arterial Hypertension - L. V. Topchieva; O.V. Balan; V. A. Korneeva; I. E. Malysheva (Bulletin of Experimental Biology and Medicine, 2019)

Analysis of the Association of TNF -238G>A Gene Polymorphism with the Risk of Rheumatoid Arthritis Development in Russian Population in the Republic of Karelia - I. E. Malysheva; L. V. Topchieva; O. V. Balan; I. M. Marusenko; O. Yu. Barysheva; I. V. Kurbatova (Bulletin of Experimental Biology and Medicine, 2018)

Low-temperature evolution of OH bands in synthetic forsterite, implication for the nature of H defects at high pressure - J. Ingrin; J. Liu; C. Depecker; S. C. Kohn; E. Balan; K. J. Grant (Physics and Chemistry of Minerals, 2013)

AFEX Pretreatment and Enzymatic Conversion of Black Locust (Robinia pseudoacacia L.) to Soluble Sugars - Rebecca J. Garlock; Yi Siang Wong; Venkatesh Balan; Bruce E. Dale (BioEnergy Research, 2012)

Organic matter governs N and P balance in Danube Delta lakes - E. Durisch-Kaiser; A. Doberer; J. Reutimann; A. Pavel; S. Balan; S. Radan; B. Wehrli (Aquatic Sciences, 2011)

Strategy for Identification of Novel Fungal and Bacterial Glycosyl Hydrolase Hybrid Mixtures that can Efficiently Saccharify Pretreated Lignocellulosic Biomass - Dahai Gao; Shishir P. S. Chundawat; Tongjun Liu; Spencer Hermanson; Krishne Gowda; Phillip Brumm; Bruce E. Dale; Venkatesh Balan (BioEnergy Research, 2010)

Induced modifications of kaolinite under ionizing radiation: an infrared spectroscopic study - C. Fourdrin; E. Balan; T. Allard; C. Boukari; G. Calas (Physics and Chemistry of Minerals, 2009)

Metal chelate affinity precipitation of RNA and purification of plasmid DNA - Sindhu Balan; Jason Murphy; Igor Galaev; Ashok Kumar; George E. Fox; Bo Mattiasson; Richard C. Willson (Biotechnology Letters, 2003)

One-pot microwave assisted preparation of pyrazoloquinazolinone libraries - Thomas E. Vasquez; Thomas Nixey; Balan Chenera; Vijay Gore; Michael D. Bartberger; Yaxiong Sun; Christopher Hulme (Molecular Diversity, 2003)

Incorporation of Cr 3+ in dickite: a spectroscopic study - E. Balan; T. Allard; G. Morin; G. Calas (Physics and Chemistry of Minerals, 2002)

57 Fe Mössbauer spectroscopy of tektites - S. Rossano; E. Balan; G. Morin; J.-P. Bauer; G. Calas; C. Brouder (Physics and Chemistry of Minerals, 1999)